Associations of prenatally detected choroid plexus cysts with biochemical risk for congenital disorders - Serapinas, Danielius; Sukys, Marius; Bardziliauskas, Povilas (Medical Studies/Studia Medyczne, 2014)
Introduction: C horoid plexus cysts are one of the foetus ultrasonography findings that raise parents’ concerns about their child’s health. Usually cysts are found in an estimated 1% all performed ultrasonographies. Aim of the research: To evaluate the risk of Down syndrome, Edward’s syndrome and neural tube defect when choroid plexus cysts are found. Material and methods : The risks of Down syndrome, Edward’s syndrome and neural tube defect were calculated by using second-trimester biomarkers (a-fetoprotein, human choriongonadotropin, unconjugated estriol) for patients with choroid plexus cysts. A control group was selected randomly with calculated risks and without any abnormal ultrasonography findings. These risks were compared between the two groups. Results: Twelve pregnancies with diagnosed choroid plexus cysts were included in this study during the year 2012. Choroid plexus cyst findings during this case/control study have shown that only one case from the test group had progressed to more serious foetal aberrations (Edward’s syndrome); nonetheless, this progression did not influence statistically significant changes in the test and control groups. No statistically significant changes between the risks of disorders according the PRISCA method were observed in the appearance of Down syndrome or neural tube defect.  Conclusions : There is no data that choroid plexus cysts increase the risk of Down syndrome, Edward’s syndrome and neural tube defect.